Reproducibility of Dynamic Contrast-Enhanced MRI in Renal Cell Carcinoma. Issue 37 (September 2015) - Wang, Haiyi; Su, Zihua; Ye, Huiyi; Xu, Xiao; Sun, Zhipeng; Li, Lu; Duan, Feixue; Song, Yuanyuan; Lambrou, Tryphon; Ma, Lin; Roviello., Giandomenico
<x xml:space="preserve">Abstract</x> Abstract The objective of this study was to investigate the intra- and interobserver as well as scan–rescan reproducibility of quantitative parameters of renal cell carcinomas (RCCs) with dynamic contrast-enhanced magnetic resonance imaging (DCE-MRI). A total of 21 patients with clear cell RCCs (17 men, 4 woman; age 37–69 years, mean age 54.6 years, mean size, 5.0 ± 2.2 cm) were prospectively recruited from September 2012 to November 2012. Patients underwent paired DCE-MRI studies on a 3.0 T MR system with an interval of 48 to 72 hours. The extended-Tofts model and population-based arterial input function were used to calculate kinetic parameters. Three observers defined the 2-dimensional whole-tumor region of interest at the slice with the maximum diameter of the RCC. Intraobserver and scan–rescan differences were assessed using paired t tests, whereas interobserver differences using two-way analysis of variance. Intra- and interobserver reproducibility and scan–rescan reproducibility were evaluated using within-subject coefficient of variation (wCoV) and intraclass correlation coefficient (ICC). There were no significant intra-, interobserver, or scan–rescan differences in parameters (all P > 0.05). All ICCs for intra- and interobserver agreements were >0.75 (P < 0.05), whereas the scan–rescan agreement was moderate to good; Ve (0.764, 95% confidence interval [CI]: 0.378–0.925) and Kep (0.906, 95% CI: 0.710–0.972) had higher ICC than Ktrans (0.686; 95% CI: 0.212–0.898) and Vp (0.657; 95% CI: 0.164–0.888). In intra- and interobserver variability analyses, all parameters except Vp had low wCoV values. Ktrans and Ve had slightly lower intraobserver wCoV (1.2% and 0.9%) compared with Kep (3.7%), whereas all 3 of these parameters had similar interobserver wCoV values (2.5%, 3.1%, and 2.9%, respectively). Regarding scan–rescan variability, Ktrans and Kep showed slightly higher variation (15.6% and 15.4%) than Ve (10.1%). Vp had the largest wCoV in all variability analyses (all >30%). DCE-MRI demonstrated good intra- and interobserver reproducibility and moderate to good scan–rescan performance in the assessment of RCC using Ktrans, Kep, and Ve as parameters under noncontinuous scanning mode. Vp showed poor reproducibility, and thus may not be suitable for this scanning protocol.